Antropologia wolności w filozofii Sartre’a i Lévinasa - Błaszczyk, Marek (Studia Europaea Gnesnensia, 2016)
This paper sets out to outline the singular nature of the dimension of anthropology of freedom in the philosophies of Jean-Paul Sartre and Emmanuel Lévinas, the leading existentialists of the 20th century. It seems that the phenomenon of human freedom, one of the fundamental issues in philosophical anthropology, in particular in the humanist reflection, proves to be problematic when one seeks to elucidate it without ambiguity. This becomes even more difficult given that it prompts further momentous intellectual quandaries, mostly those concerned with the nature of the meaning of existence itself. The concepts advanced by Sartre and Lévinas – although they represent different visions of the human – undoubtedly provide much philosophical inspiration for all kinds of reflection on the vital issue of freedom.